Concert Lighting: Techniques, Art and Business, Third Edition - Moody, James (Elsevier, 2011)
Get ready to pack your bags and go on tour with the most trusted and comprehensive text for concert lighting. With a special focus on rock and roll, learn how to use computer aided drafting, moving luminaires, learn about the people and the history that shaped the field and more. Expand your design possibilities by learning about cross-media use of concert lighting techniques and their application in film, video, theatre and the corporate world. From snagging those precious contracts to knowing the best equipment to use to designing a show, Concert Lighting: Techniques, Art and Business covers everything you need to know.